Maquiavel Segretario (1498-1512), guerra e política em I Primi Scritti Politici - Silva, Walter Franco Lopes da (2012)
This research aims at addressing Machiavelli s I primi scritti politici written during the philosopher s fourteen years of involvement in politics, social conflicts and military events as Secretary to the Florentine Republic s Second Chancellery, as well as when working as Secretary to the dei Dieci di Libertà e Balía. Central to this investigation is the understanding of I primi scritti politici as an important group of writings whose fundamental nature is to bring about new debates in the fields of politics, war and social conflicts within the Florentine Republic from the early XVI Century. In addition to that, this investigation aims at considerate I primi scritti politici as the launching of Machiavelli process of thinking. Accordingly, one intends to comprehend this philosopher s process of thinking in relation to the fields of diplomacy, war and politics when in charge of a quite specific position within the Government of the Florentine Republic. Furthermore, in order to comprehend Machiavelli s infant process of thinking as a philosopher, one needs to position it within both the Florentine Government s administrative and power structures. Since this research addresses Machiavelli thinking in the fields of political and military powers in the context of the Florentine Republic, it was taken into consideration that the thinking itself reflects on a theoretical level the presumed attempt to put together the Chancellery s political-administrative and written praxis within an historical context of Florence from the years of 1489-1512. Notwithstanding this, the understanding of such philosophical thought from a historical perspective demands the comprehension of the philosopher s own universality of thinking not bind to the so-called spread of rudimentary political realism so present at that time. By the reading of I primi scritti politici, in addition to a reflexion about his experience in the Florentine Chancellery, one may comprehend the reasons behind the defence of the militia project and the consequential debate about the maintenance of freedom in Florence. Therefore, through the reconstruction of the precise political and military context - as well as logistical, legal and theoretical difficulties existent - one can understand the hardships encountered by this thinker. Hence, one shall argue that Machiavelli s experience as Secretary offered him backgrounds needed to bring about a strategy to put into place the militia project in line with the broader need to maintain freedom. By backing a military power financed and supported by Florence, Machiavelli brought a larger political project into the arena, focused on State defence and territorial administration backed on the removal of the mercenary forces from the Florentine scene. These ideas can be found on the philosopher s later works on politics, war and defence in his